2016
DOI: 10.1242/jcs.181586
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional imaging of the intracellular assembly of a functional viral RNA replicase complex

Abstract: Positive-strand RNA viruses, which can be devastating pathogens in humans, animals and plants, replicate their genomes on intracellular membranes. Here, we describe the three-dimensional ultrastructural organization of a tombusvirus replicase in yeast, a valuable model for exploring virus-host interactions. We visualized the intracellular distribution of a viral replicase protein using metal-tagging transmission electron microscopy, a highly sensitive nanotechnology whose full potential remains to be developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 44 publications
0
88
0
Order By: Relevance
“…Since then, many studies have demonstrated the power of these methods. Structures harboring the VRCs such as single-membrane spherules and double membrane vesicles have been studied in detail within the replication organelles of West Nile Virus (Gillespie et al, 2010), HCV (Romero-Brey et al, 2012), coxsackievirus B3 (Limpens et al, 2011), Bunyamwera virus (Fontana et al, 2008), Rubella virus (Fontana et al, 2010), Tombusvirus (Fernández de Castro et al, 2017a), a cardiovirus (Melia et al, 2018) and the human reovirus (Fernández de Castro et al, 2014a;Tenorio et al, 2018). The reovirus replication neoorganelle visualized in 3D with two different methods is shown in Fig.…”
Section: D Imaging/tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, many studies have demonstrated the power of these methods. Structures harboring the VRCs such as single-membrane spherules and double membrane vesicles have been studied in detail within the replication organelles of West Nile Virus (Gillespie et al, 2010), HCV (Romero-Brey et al, 2012), coxsackievirus B3 (Limpens et al, 2011), Bunyamwera virus (Fontana et al, 2008), Rubella virus (Fontana et al, 2010), Tombusvirus (Fernández de Castro et al, 2017a), a cardiovirus (Melia et al, 2018) and the human reovirus (Fernández de Castro et al, 2014a;Tenorio et al, 2018). The reovirus replication neoorganelle visualized in 3D with two different methods is shown in Fig.…”
Section: D Imaging/tomographymentioning
confidence: 99%
“…Scale bar: 100 nm in mainfield in A; 50 nm in inset in A. Modified from Fernández de Castro, I., Fernández, J.J., Barajas, D., Nagy, P.D., Risco, C., 2017a. Three-dimensional imaging of the intracelular assembly of a functional viral RNA replicase complex.…”
Section: Clonable Tags For Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses complete their entire replication cycle in the host cell cytoplasm. To generate sites for their genomic RNA replication, positive-strand RNA viruses expand and rearrange host cellular membranes (Fernández de Castro et al, 2017; den Boon et al, 2010; Kovalev et al, 2016; Paul and Bartenschlager, 2013; Paul et al, 2014; Romero-Brey and Bartenschlager, 2014). Such membrane-associated RNA replication sites are thought to concentrate essential viral and host factors, and to organize successive steps for efficient viral RNA synthesis (Atasheva et al, 2010; Neuvonen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent developments in light and electron microscopy are having a significant impact in virology. In particular, live-cell microscopy, super-resolution microscopy, correlative light and electron microscopy (CLEM) and 3D imaging are now fundamental tools for studying virus-cell interactions (Bykov et al, 2016;Fernandez de Castro et al, 2017;Francis and Melikyan, 2018;Risco et al, 2014;Witte et al, 2018). Microscopy is also a powerful tool for studying antivirals.…”
Section: Imaging For Studying Antiviralsmentioning
confidence: 99%